2020
DOI: 10.1186/s41100-020-00264-1
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of glycated albumin as a predictor of mortality in chronic hemodialysis patients with diabetes: a multi-center, prospective cohort study

Abstract: Background: The association of glycated albumin (GA) with mortality is unclear in chronic hemodialysis patients with diabetes. We investigated the usefulness of GA by comparing it with hemoglobin A1c (HbA1c) in this patient population. Research design and methods: This was a multi-center, prospective cohort study of 841 Japanese chronic hemodialysis patients with diabetes. There were 235 women and 606 men included, with a mean age of 64 years. The primary and secondary endpoints were the incidence of all-cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These results suggest a need to set the target GA value for glycemic control based on consideration of such factors as the use of antidiabetic agents, nutritional status, and patient background, such as cancer development status. Furthermore, based on the multicenter prospective observational study of 841 chronic dialysis patients with diabetes for a mean study period of 3.1 years, GA levels could be a prognostic factor in predicting atherosclerotic cardiovascular disease (ASCVD)-related mortality [16]. Overall, it was suggested that GA might be a more suitable parameter than HbA1c for accurately predicting the prognosis of dialysis patients with diabetes.…”
Section: Target Ga Levels In Hemodialysis Patients From Observational...mentioning
confidence: 99%
“…These results suggest a need to set the target GA value for glycemic control based on consideration of such factors as the use of antidiabetic agents, nutritional status, and patient background, such as cancer development status. Furthermore, based on the multicenter prospective observational study of 841 chronic dialysis patients with diabetes for a mean study period of 3.1 years, GA levels could be a prognostic factor in predicting atherosclerotic cardiovascular disease (ASCVD)-related mortality [16]. Overall, it was suggested that GA might be a more suitable parameter than HbA1c for accurately predicting the prognosis of dialysis patients with diabetes.…”
Section: Target Ga Levels In Hemodialysis Patients From Observational...mentioning
confidence: 99%